Growth control, interface behavior, band alignment, and potential device applications of 2D lateral heterostructures. (29th November 2017) - Zhao, Jijun; Cheng, Kai; Han, Nannan; Zhang, Junfeng
Abstract : Two‐dimensional (2D) lateral heterostructures open a new avenue for intentional design of novel 2D devices with superior electronic and optoelectronic properties. Since 2012, many groups have successfully synthesized lateral graphene/ h ‐BN heterostructures on metal substrates and the fabrication of in‐plane heterostructures of transition metal dichalcogenides has also been reported since 2014. In this review, we first present an overview on recent progress of the experimental fabrications of 2D lateral heterostructures, along with the growth mechanism from atomistic simulations. The atomic structures of interfaces, electronic and thermal transport properties across interfaces for some 2D lateral heterojunctions are then discussed. Our current theoretical understanding on the band alignments and electronic properties as well as potential device applications of these lateral heterostructures are summarized. Finally, we give a perspective on this fast‐growing field. WIREs Comput Mol Sci 2018, 8:e1353. doi: 10.1002/wcms.1353 This article is categorized under: Structure and Mechanism > Computational Materials Science Abstract : Schottky barrier height and band alignment of 2D lateral metal/semiconductor and semiconductor/semiconductor heterostructures.